2017
DOI: 10.1177/1362168817718574
|View full text |Cite
|
Sign up to set email alerts
|

‘A more inclusive mind towards the world’: English language teaching and study abroad in China from intercultural citizenship and English as a lingua franca perspectives

Abstract: With the status of English as a global lingua franca (ELF), English is no longer the sole property of its Anglophone native English speakers (NES) problematising the current dominance of Anglophone cultures and NES in the field of English language teaching (ELT).The notion of intercultural citizenship education offers a critical alternative model in language education. To investigate how ELF, intercultural approaches and the concept of intercultural citizenship might be integrated within the field of ELT, a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
67
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 43 publications
6
67
1
1
Order By: Relevance
“…Therefore, in addition to intellectual development, university students also need to gain a better sense of themselves and their relationships with others and the world. In other words, they need to cultivate a global perspective (GP) to develop as a global citizen, not only in language learning but also in general education (Baker & Fang, 2019;Fang & Baker, 2018;Goren & Yemini, 2017;). As English has evolved as a global language in recent decades (Crystal, 2012), it has become more important to acquire a GP through the use of English.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in addition to intellectual development, university students also need to gain a better sense of themselves and their relationships with others and the world. In other words, they need to cultivate a global perspective (GP) to develop as a global citizen, not only in language learning but also in general education (Baker & Fang, 2019;Fang & Baker, 2018;Goren & Yemini, 2017;). As English has evolved as a global language in recent decades (Crystal, 2012), it has become more important to acquire a GP through the use of English.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the intercultural skills that students were found to have in the present study, Liu and Fang (2017) found superficial understanding of Chinese culture in an efl Chinese context. Fang (2018) also found that efl Chinese students gain their understanding and experience about intercultural communication more outside the classroom. The findings of this study support introducing cda tools to enhance intercultural skills among efl students.…”
Section: Discussionmentioning
confidence: 84%
“…Liu and Fang (2017) found that most efl Chinese students demonstrated a belief in the importance of intercultural awareness. Fang (2018) found that efl Chinese students have positive attitudes toward intercultural citizenship and the English language. Similarly, Ko (2013) found that students develop critical consciousness of ideas that have been taken for granted after employing cda in a critical-based literacy reading class.…”
Section: Discussionmentioning
confidence: 93%
“…Considering the fact that not all foreign students have good English skills, thus this has become a challenge to foreign students who study English and to lecturers who teach English. A cultural approach is needed to address these challenges, such as what Fang & Baker (2018) stated, "More in-depth and critical approaches to teaching language, culture and intercultural communication in ELT are needed which foster and cultivate students' sense of intercultural citizenship. "…”
Section: Discussionmentioning
confidence: 99%